A low background D–A–D type fluorescent probe for imaging of biothiols in living cells. Issue 32 (30th July 2018) - Chen, Dugang; Yang, Juliang; Dai, Jun; Lou, Xiaoding; Zhong, Cheng; Yu, Xianglin; Xia, Fan
Abstract : The design strategy of a bioprobe based on a D–A–D type fluorophore was discussed, andCBFB constructed by this kind of fluorophore showed specific biothiol recognition in living cells. Abstract : Two probes, structurally symmetricCBFB and asymmetricCBFM, constructed by a D–A–D (donor–acceptor–donor) type curcuminoid as the fluorophore and the DNBS (2, 4-dinitrobenzenesulfonyl) group as the biothiol recognition site were designed and synthesized here. The DNBS group can quench the emission of the fluorophore by the PET (photoinduced electron transfer) process, and in the presence of biothiols, the emission of the probe was switched on as a result of the cleavage of the quencher by a nucleophilic aromatic substitution reaction. Experimental analyses and theoretical calculations revealed that two recognition moieties in the molecule can quench the fluorescence more efficiently, therefore, CBFB showed a much higher SNR (signal to noise ratio) thanCBFM in biothiol detection with an emission maximum at 610 nm. This "low background" and "turn-on" fluorescent probe, CBFB, was successfully utilized to map endogenous biothiols in living cells.